ANALISIS EFISIENSI STRUKTUR RANTAI PASOK AGRIBISNIS CABAI MERAH BESAR DI DESA SINDULANG, KABUPATEN SUMEDANG - Eddy Renaldi; Pandi Pardian; Hanifa Kuswatim, Salsabila (Jurnal Pertanian Agros, 2025)
This study aims to analyze the efficiency of red chili agribusiness supply chain structures in Sindulang Village, Cimanggung Subdistrict, Sumedang Regency. Efficiency is measured by indicators such as distribution chain length, production cost (HPP), marketing margin, farmer’s share, and cash flow cycle. The research applied a qualitative case study approach using descriptive and diagnostic analysis. Results reveal three main supply chain structures: independent farmers, cooperative-partnered farmers, and company-partnered farmers. The independent farmer model was the most efficient, having the shortest chain, lowest HPP, smallest marketing margin, and highest farmer’s share (50%). The cooperative model was the least efficient, with the lowest farmer’s share (38%), highest HPP, and the longest cash cycle. The company-partnered model ranked moderate in efficiency. These findings emphasize that supply chain efficiency is significantly influenced by institutional structure, distribution system, and the integration of information among actors.